PERTANGGUNG JAWABAN HUKUM KASIR (TELLER) AKIBAT KELALAIAN DALAM TRANSAKSI KEUANGAN NASABAH (STUDI PADA PT. BNI KCU USU MEDAN) - Finita Serena Hutabarat; Sunarmi Sunarmi; Runtung Runtung; Utary Maharany Barus (Universitas Sumatera Utara, 2016)
ABSTRACT Banking is something which is related to banks, including institutional, business, method, and process of implementing its business. It plays an important role in clients’ financial transaction which is conducted by tellers. In this case, tellers are not without errors which harm the clients, and thus they have to take the responsibility for their errors. USU Main Branch Office of PT Bank Negara Indonesia is one of the branch offices in which the tellers make errors in clients’ financial transaction. The problems of the research were as follows: 1) how about the right and the obligation of tellers in the work contract between tellers and PT Bank Negara Indonesia, 2) how about the errors made by the tellers in conducting clients’ financial transaction at USU Main Branch Office of PT Bank Negara Indonesia, and 3) how about their responsibility for their errors in conducting clients’ financial transaction which harm the clients at USU Main Branch Office of PT Bank Negara Indonesia. Tellers’ responsibility is in the civil case in the form of an amount of money. Here, they have to and are fully responsible for settling the errors by compensating the clients’ nominal damages and the cost which was spent in doing the financial transaction. The obstacle is that when the nominal damage is too big, the tellers cannot afford to compensate it. Therefore, the management of the Bank will take over the responsibility, while the tellers will have sanction imposed on them. It is recommended that “other internal regulations” should be reaffirmed so that it will be obvious and certain which regulations that have to be complied by the tellers, and formless system in cash deposit transaction should be reviewed. Transparent rules of tellers’ responsibility in carrying out their job should be made clearer and the trade union of BNI should be involved in imposing sanction to tellers who make errors. Keywords : Errors, Financial Transaction, Responsibility